2014
DOI: 10.1051/swsc/2014005
|View full text |Cite
|
Sign up to set email alerts
|

A semi-analytical foreshock model for energetic storm particle events inside 1 AU

Abstract: We have constructed a semi-analytical model of the energetic-ion foreshock of a CME-driven coronal/interplanetary shock wave responsible for the acceleration of large solar energetic particle (SEP) events. The model is based on the analytical model of diffusive shock acceleration of Bell (1978), appended with a temporal dependence of the cut-off momentum of the energetic particles accelerated at the shock, derived from the theory. Parameters of the model are re-calibrated using a fully time-dependent self-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…Within the estimated uncertainties, the powerlaw exponent a in 15 out of 27 SEP events lies between ∼0.75-2.75 and is comparable to the range of values obtained by Cohen et al (2005), as shown by the yellow shaded region. Also, a varies between ∼−0.33-3.9, which is roughly consistent with the typical range of ∼0.5-7 proposed recently by Schwadron et al (2015b); in this model a<1 implies a weak dependence of // l on the ionʼs Q/M ratio, while a>1 indicates that // l depends strongly on Q/M (also see Li et al 2009;Battarbee et al 2011Battarbee et al , 2013Vainio et al 2014). We note that η in 27 events lies between −1.87 and 2.33; η in 15 events lies within the range ∼0.7-1.2 reported by Cohen et al (2005).…”
Section: Properties Of Near-sun Cme Shocks and Turbulence Conditionssupporting
confidence: 88%
“…Within the estimated uncertainties, the powerlaw exponent a in 15 out of 27 SEP events lies between ∼0.75-2.75 and is comparable to the range of values obtained by Cohen et al (2005), as shown by the yellow shaded region. Also, a varies between ∼−0.33-3.9, which is roughly consistent with the typical range of ∼0.5-7 proposed recently by Schwadron et al (2015b); in this model a<1 implies a weak dependence of // l on the ionʼs Q/M ratio, while a>1 indicates that // l depends strongly on Q/M (also see Li et al 2009;Battarbee et al 2011Battarbee et al , 2013Vainio et al 2014). We note that η in 27 events lies between −1.87 and 2.33; η in 15 events lies within the range ∼0.7-1.2 reported by Cohen et al (2005).…”
Section: Properties Of Near-sun Cme Shocks and Turbulence Conditionssupporting
confidence: 88%
“…Consequently, the applied numerical acceleration models contain several parameters, some of which can only be determined in an ad-hoc manner. As an example of such an approach, Vainio et al (2014) performed Monte Carlo simulations in their state-ofthe-art semi-analytical foreshock model from about 6 to 60 solar radii. More similar studies together with data comparison are called for to gain better understanding of the ICME shock acceleration.…”
Section: Particle Acceleration At Icme Shocksmentioning
confidence: 99%
“…Further development has been pointed towards a completely self-consistent dynamic modelling of particle acceleration (for the results, see e.g. Vainio & Laitinen 2007Ng & Reames 2008;Battarbee et al 2011;Vainio et al 2014).…”
Section: Introductionmentioning
confidence: 99%